Experimental study of the effects of excess air ratio on combustion and emission characteristics of the hydrogen-fueled rotary engine. (13th September 2021) - Meng, Hao; Ji, Changwei; Yang, Jinxin; Wang, Shuofeng; Chang, Ke; Xin, Gu
Abstract: To investigate the property of the promising and eco-friendly hydrogen-fueled rotary engine, the effect of excess air ratio on the combustion and emission characteristic of it was explored by experiment. The test was conducted under 1500 rpm and 5 CAD ADTC ignition timing. The test results demonstrated that with the decrease of excess air ratio from 2 to 0.85, the thermal efficiency of the hydrogen-fueled rotary engine increases first and then decreases. Besides, increasing MAP is beneficial to improve thermal efficiency. Among the tested condition, the highest brake thermal efficiency is realized when the rotary engine operates at 1.4 excess air ratio and 88 kPa MAP, about 18.34%. And the excellent HC and NO emissions can be obtained at the highest efficiency point. Besides, with the decrease of excess air ratio and the increase of load, the stability and flame development period gradually decrease. With a decreased excess air ratio, the flame propagation period decrease first and then increases, whereas work capacity and thermal efficiency increase first and then decrease. For NO emission, it will increase sharply near the equivalent ratio and gradually decrease after rich combustion. Also, according to the analytical model, it is found that the power performance of the rotary engine depends on the trade-off relationship of in-cylinder pressure and its angle of action. Highlights: A rotary engine was modified to run on hydrogen. The effects of excess air ratio on combustion and emission were studied. The best efficiency is obtained when the excess air ratio equals 1.4. An analytical model is presented and the reasonability also be proved. The emission corresponding to the best efficiency point is excellent.